Bancah: Local Knowledge, Cultural Adaptation, and its Challenges - Delfi, Maskota; Arifin, Zainal; Pujiraharjo, Sidarta; Jelly, Jelly; Irwandi, Ade (Bina Nusantara University, 2025)
The research explains the concept of bancah, which translates to